Un scanner de conteneurs en « Terre Promise » camerounaise : adopter et s’approprier une technologie de contrôle - Thomas Cantens (L'Espace Politique)
This article is based on an ethnographic fieldwork conducted between 2006 and 2010 in an African Customs Administration. A specific event - the adoption and implementation of a container scanner by the administration – is an interesting opportunity to examine two questions related to control technology in the particular context of African borders. The first question is the adoption of a technology: how does a tool become an instrument that renews the meaning of the control at borders? A tentative answer is provided by a description of public and private rationales that led to the adoption of container scanners in many African customs. The second question is the effectiveness of a technique that is deployed within border spaces that are quantified and represented through economics. The answer examines the difficulties in calculating this efficiency as a notion vested with the notion of profitability and highlights the strength of technology as a technical idiom satisfying the promise of reform.